Ergonomic job redesign for multitask packaging work by using revised NIOSH lifting equation - Muhammad Thaqib, Kamaruzzaman (2008)
The purpose of this study is to analyze the existing operation of a manual multitask packaging work task which is hazardous to a worker and then suggest the improvements by providing practical guidelines ergonomically. The work task was suggested to be redesigned ergonomically and improved by looking for clues and reviewing previous complaints, by observing the work activities, and by talking to the workers, supervisors, and managers. Several National Institute for Occupational Safety and Health (NIOSH) assessment tools of assessing work task was conducted to quickly detect problem work tasks. The result of the analysis did show that the evaluated work task is physically stressful to even healthy workers but follow up actions were not done because the suggested improvements were not accepted and implemented. Despite the fact that the suggested improvements were not accepted, the ergonomic practical guidelines were still established generally and may only be reliable if were to be used in the evaluated section of BI Technologies Corporation Sdn. Bhd.